Effect of grain shape elongation in direction and perpendicular to current stream (conductive or insulator) on the electrical characteristics of mixtures - Mohamed Mahmoud Gomaa (Scientific Reports)
Abstract The shape elongation of grains, in mixtures, can have an effect on the electrical characteristics. Grain size and structural changes can impact the dielectric, and electrical properties of materials. The electrical properties of natural mixtures are influenced by their arrangement and shape. Insulating grains block potential pathways for electricity between electrodes. One key factor is grain shape elongation and how it aligns with the electric current. If the long part of the conductor grains lines up with the stream of current, then it will show high conductivity and an early critical percolation threshold. The critical percolation threshold decreases when the conductor is extended with the stream of current. Conductor elongated with the current stream increases the current flow. When the conductor is elongated perpendicular to the current stream, from sphere to needle, no perceptible alterations upon the associated critical threshold take effect. When the insulator is elongated with the stream of current the critical percolation threshold does not change significantly. The critical percolation threshold increases when insulator elongation perpendicular to the current direction. The elongated insulator perpendicular to the current’s stream hinders the current’s flow. The EMT offers a simulation to contain the variations in dielectric constant and conductivity across different concentrations. This is the first time to discuss the direction of elongation of conductor or insulator grains, in a mixture, in parallel or perpendicular to the stream of the current.